Legal Certainty of Execution of Bankrupt as Collateral Charged by Mortgage Rights - Nuslan, Feizy Veranda Adeline; Kusumawati, Lanny (Journal of Economic and Business Law Review, 2025)
The legal framework governing bankruptcy and mortgage rights has been stated in Law Number 37 of 2004 concerning Bankruptcy and Suspension of Debt Payment Obligations (hereinafter referred to as: KPKPU Law) and Law Number 4 of 1996 concerning Mortgage Rights on Land and Objects Related to Land (hereinafter referred to as UUHT). Normatively, the two regulations are designed to complement each other. However, in its implementation, there is disharmony between Article 56 paragraph (1) of the KPKPU and Article 6 and Article 21 of the UUHT. Therefore, this study focuses on the analysis of legal protection for creditors holding mortgage rights in the condition of debtor bankruptcy and reviews the aspect of legal certainty in the process of executing collateral assets. This study adopts three main approaches, namely the legislative approach, the conceptual approach, and the case approach